Effectiveness of digital data acquisition technologies in the fabrication of maxillofacial prostheses - A systematic review - Nandita Suresh; Chandrashekar Janakiram; Suresh Nayar; V.N. Krishnapriya; Anil Mathew (Elsevier, 2022)
Objective: The systematic review was designed to review and analyze the outcomes of various digital data acquisition technologies used for treatment planning in the prosthetic rehabilitation of maxillofacial defects. Methods: The review protocol was registered in PROSPERO data with registration number: CRD42020188415. The PICOS inclusion criteria was employed in the systematic review. An electronic search (PubMed, databases) yielded twenty-eight eligible case reports. The qualitative methodological assessment was done according to an article that provided criteria for special considerations in evaluating case reports. It consisted of four questions, each carrying grading of 0, 1, and 2. During the full-text screening, the reviewers shortlisted six outcomes (time, aesthetics, cost, dimensional accuracy, patient satisfaction, and fabrication process) and graded (0, 1, 3) according to the outcomes they met. Results: The majority of the included case reports used LASER scanners. Auricular and orbital defects were the highest reported cases. In nasal and orbital defects, the mean outcome of the shorter time required for the fabrication was the highest. In auricular prostheses, the mean outcome of dimensional accuracy was highest. In facial prostheses, aesthetics, dimensional accuracy, and patient satisfaction had the highest mean outcome whereas, in obturators, the shorter time required, dimensional accuracy, and patient satisfaction had the highest mean outcome. A total of 18 studies were graded as highly significant studies according to the methodological qualitative assessment. Conclusion: LASER scanning systems in nasal prostheses, LASER scanners and combination of CT scan and digital photography in auricular prostheses, digital photography and stereophotogrammetry in case of large facial defects and combination of MRI and CT scan for obturators appeared to be a superior method of digital data acquisition.